Barns of New York : Rural Architecture of the Empire State - Falk, Cynthia G. (Book collections on Project MUSE., 2012)
Barns of New York explores and celebrates the agricultural and architectural diversity of the Empire State-from Long Island to Lake Erie, the Southern Tier to the North Country-providing a unique compendium of the vernacular architecture of rural New York. Through descriptions of the appearance and working of representative historic farm buildings, Barns of New York also serves as an authoritative reference for historic preservation efforts across the state. Cynthia G. Falk connects agricultural buildings-both extant examples and those long gone-with the products and processes they made and make possible. Great attention is paid not only to main barns but also to agricultural outbuildings such as chicken coops, smokehouses, and windmills. Falk further emphasizes the types of buildings used to support the cultivation of products specifically associated with the Empire State, including hops, apples, cheese, and maple syrup. Enhanced by more than two hundred contemporary and historic photographs and other images, this book provides historical, cultural, and economic context for understanding the rural landscape. In an appendix are lists of historic farm buildings open to the public at living history museums and historic sites. Through a greater awareness of the buildings found on farms throughout New York, readers will come away with an increased appreciation for the state's rich agricultural and architectural legacy.